Characterization of the symbiont Rickettsia in the mirid bug Nesidiocoris tenuis (Reuter) (Heteroptera: Miridae). Issue 6 (December 2014) - Caspi-Fluger, A.; Inbar, M.; Steinberg, S.; Friedmann, Y.; Freund, M.; Mozes-Daube, N.; Zchori-Fein, E.
Abstract Nesidiocoris tenuis (Reuter) (Heteroptera: Miridae) is an omnivorous insect used for biological control. Augmentative release and conservation of N. tenuis have been used for pest control in tomato crops. Intracellular bacterial symbionts of arthropods are common in nature and have diverse effects on their hosts; in some cases they can dramatically affect biological control. Fingerprinting methods showed that the symbiotic complex associated with N. tenuis includes Wolbachia and Rickettsia. Rickettsia of N. tenuis was further characterized by sequencing the 16S rRNA and gltA bacterial genes, measuring its amount in different developmental stages of the insect by real-time polymerase chain reaction, and localizing the bacteria in the insect's body by fluorescence in situ hybridization. The Rickettsia in N. tenuis exhibited 99 and 96% similarity of both sequenced genes to Rickettsia bellii and Rickettsia reported from Bemisia tabaci, respectively. The highest amount of Rickettsia was measured in the 5th instar and adult, and the symbionts could be detected in the host gut and ovaries. Although the role played by Rickettsia in the biology of N. tenuis is currently unknown, their high amount in the adults and localization in the gut suggest that they may have a nutritional role in this insect.